Aerosol composition and sources during high and low pollution periods in Ningbo, China - Xu, Jing-Sha; Xu, Hong-Hui; Xiao, Hang; Tong, Lei; Snape, Colin E.; Wang, Cheng-Jun; He, Jun (Elsevier, 2016)
Due to the rapid industrialization of the Yangtze River Delta (YRD) region in China, heavy air pollution episodes have occurred frequently over the past five years which are of great concern due to their environmental and health impacts. To investigate the chemical characteristics of the highly polluted aerosols in this region, a sampling campaign had been conducted in Ningbo from 3 December 2012 to 27 June 2013, during which a month long high pollution episode had been captured. Daily average PM2.5 concentrations during high and low pollution periods were 111 μg m−3 and 53 μg m−3, respectively. The most polluted day was 8 January 2013 with a PM2.5 concentration up to 175 μg m− 3. To understand the origin of the highly polluted aerosols, meteorological conditions, air mass backward trajectories, distribution of fire spots in surrounding areas and various categories of aerosol pollutants were analyzed, including trace metals, inorganic species, PAHs and anhydrosugars. Total metal concentrations were 3.8 and 1.6 μg m−3 for the high and low pollution episodes, respectively, accounting for 3.4% and 3.1% of the total PM2.5 mass. Total concentrations of ionic species accounted for more than 50.0% of the PM2.5 by mass, with dominant ions (nitrate, sulfate, ammonium) accounting for over 42.0% of the PM2.5 mass concentrations in both periods. During the high pollution episode, enhanced Cd–Pb and biomarker (levoglucosan, mannosan) levels indicated the contributions from coal combustion, traffic and biomass burning to fine aerosol PM2.5. The average diagnostic ratio of Fla/(Fla + Pyr) was 0.54 in high pollution episode, which was intermediate between that for wood (> 0.50) and coal combustion (0.58). BaP/Bpe was 0.49 and 0.30 for the highly and lightly polluted aerosols respectively, associated with the significant non-traffic emissions (< 0.60). In addition, stagnant weather conditions during the high pollution period and long-range transport of air masses from heavy industries and biomass burning from northern China to Ningbo could be considered as the main factors for the formation of the aerosols during high pollution period.